PEMILIHAN KEPALA DAERAH OLEH DEWAN PERWAKILAN RAKYAT DAERAH PASCA PUTUSAN MK NO. 85/PUU-XX/2022: Regional Head Elections by People’s Legislative Council after the Prevailing of Constitutional Court Decision No 85/PUU-XX/2022 - Baharuddin Riqiey (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The regional head election can be held in two models, namely direct election or election through People’s Legislative Council. Both are constitutional as stated in Constitutional Court Decision No. 97/PUU-XI/2013. However, after the prevailing of Constitutional Court Decision No. 85/PUU-XX/2022, which does not differentiate between general election and regional head election, then as one of the principles contained in Article 22E of the 1945 Constitution of the Republic of Indonesia, namely the principle of